Age Peculiarities of Lipid Peroxidation in Rats After Extreme Cryoeffects - Babiychuk, V. G. (Problems of Cryobiology and Cryomedicine, 2006)
The obtained results suppose that an important mechanism of potentiative extreme cryoeffect (ECE) is a positive influence on pro-oxidative and anti-oxidative state of an organism of the animals under study. This effect has been kept for a long period after the influence termination. In this case there are observed age peculiarities (higher reactivity for young animals). In a whole the activation of heart anti-oxidative system under ECE regardless age permits to increase an organism stress resistance. Chronic insufficiency of the function of anti-oxidant system is one of the causes of cardiovascular pathology development. â€œMildâ€ and short-term stress, that may be ECE, contributes to a manifested protective reaction due to early mobilization of anti-oxidant organism system.